CARBON MODIFICATION OF BITUMEN - K. V. Belyaev; I. L. Chulkova (Вестник СибАДИ, 2019)
Introduction. The causes of premature destruction of asphalt concrete coatings are aging and low quality of bitumen. The paper describes the methods for improving the bitumen properties. The authors present the review of the bitumen modification by carbon black usage. The usage of carbon black leads to structural changes in the bitumen. Therefore, the authors select carbon black additives as a promising modifiers.Materials and methods. The paper showed the characteristics of carbon modifiers and the properties of the initial bitumen.Results. The authors experimentally determined the main parameters of the modified bitumen and compared the effect of three carbon black additives on the bitumen properties. The usage of activated carbon black significantly reduced the penetration of bitumen than non-activated carbon black, however, the indicators of aging were declined.Discussion and conclusions. As a result, the solid additive’s usage increases the bitumen viscosity with other standard characteristics’ preservation, and thus improves the bitumen thermal stability. Therefore, the usage of activated carbon black in dry forms does not affect significantly on the bitumen properties in comparison with varietal N 375 grade-carbon.